Biosorption of methylene blue by sulfuric acid treated spent grated coconut (cocos nucifera) in fixed-bed column study / Mohamad Fakhrul Hisham Hashim - Hashim, Mohamad Fakhrul Hisham (Faculty of Applied Sciences, 2016)
Plant waste which comes from coconut process output was determined as new adsorbent to be analysed to optimise the efficiency of adsorbent to be used. In this study, the treated spent grated coconut, cocos nucifera was chosen to be investigated for treating dyes contaminant. Parameter or condition such as mass of adsorbent, bed depth, inlet concentration, flow rate and pH value of Methylene blue are fixed for this study. Inlet concentration used 100.0 mg/L, 1.0 g of mass adsorbent at 1.5 cm bed depth. The flow rate 12.0 m/min and pH value for MB is pH 6. Breakthrough curve resulted breakthrough time, tb is 120.8 min at volume Vb is 1450.0 mL. The amount adsorption capacity, qb at 115.0 mg/g and an exhaustion time, texh is 220.8 min with volume exhaustion, Vexh is 2650.0 mL.. Based on Thomas and Yoon-Nelson model showed that the internal diffusion mechanism and chemical nature process occur in this adsorption.